Two fluid scenario for dark energy models in a Bianchi type I universe - Qazi, Syed Nasrullah Ali (2014)
The current observations reveal the fact that the universe is expanding at an accelerating rate. The observations indicate that the driving force behind the accelerating expansion is the mysterious component known as dark energy. The only known information about dark energy is that it constitutes 73% of the total mass energy density of universe, its pressure is negative which acts as anti-gravitational force and it dominates at late times. However its nature still remains mysterious and it poses a challenge to the theoretical and observational cosmologists. Besides dark energy another mystery component in the universe that occupy large portion of universe after dark energy is dark matter. Since the nature of these dark components are relatively unknown to us, we could assume some sort of interaction between these components. The aim of this research is to study the nature of the dark energy by considering its physical quantity known as equation of state parameter ωD = pD/pD that specifies the model for dark energy. The general theory of relativity has the important role in explaining the dynamics of the universe as gravity governs the largest scale structure of the universe. Considering the fact that at present times that the universe to be in the form of perfect uid, the equation of state describes the type of matter energy present in universe. The measurements from cosmic microwave background reveals the anisotropies in the temperature and almost spatially at universe. Therefore in this research, I study the dark energy models in the framework of the anisotropic Bianchi I spacetime. The cosmological models studied here are mainly concerned with the recent epoch of universe. The behavior of the ωD is considered for two scenarios. First is the non-interacting scenario where the dark energy and dark matter are minimally coupled to each other. Second is the interacting scenario where there exists an interaction between the dark components and this is connected by an interaction term Q. I investigate the behavior of the !D parameter by considering the function of universe scale factor of two types. First is the scale factor in the form of power function law and it is found that ωD parameter for both non-interacting and interacting cases varies in the phantom region ωD = -1. Second is using the solutions of the Einstein field equation where I derive the general form of the ωD parameter for Bianchi I spacetime. Then I use the scale factor in terms of hyperbolic function with general ωD parameter. It is shown that in non-interacting case, depending on the value of the anisotropy parameter K, the dark energy EoS parameter is varying from phantom ωD = -1 to quintessence ωD = -1 whereas in interacting case EoS parameter vary in quintessence region. However, eventually all of these models tend to reach ωD = -1. Generally it is found that the behavior of the EoS parameter from all these models is that the dark energy model behaves like scalar field models such as quintessence, phantom and quintom.